Ocular and Eyelid Surgical Anatomy in Georg Bartisch’s “Ophthalmodouleia” - Lagiou, Efstathia; Laios, Konstantinos; Tsoucalas, Gregory; Zaganas, Ioannis; Detorakis, Efstathios T; Karamanou, Marianna (Scripta Medica, 2024)
Georg Bartisch, a 16th century barber surgeon, published in 1583 his treatise entitled “Ophthalmodouleia” (Greek term meaning eye service), a work in German to promote ophthalmology for his countrymen barber surgeons. Hadn’t had an academic education nor knew classical languages, he had used a triplet in terminology by using German, Hellenic and Latin nomination in his anatomical descriptions. Various accurate illustrations and a peculiar system of presentation with flap to liken an in-depth presentation were demonstrated to add prestige in his work. This raises concerns for another medical surgeon to have helped for this publication. Bartisch innovative approaches introduced various surgical tools. Cataract surgery was the epitome of his work. Anatomy of both the eye and the eyelids was there for only to serve the operation. Religion, magic and Galenic views presented barriers for Bartisch’s scientific development. However, he is considered as the patron of German School of Ophthalmology.